A remarkable new species of Nemoura (Plecoptera: Nemouridae) from Chuxiong Yi Autonomous Prefecture of Yunnan Province, China - Qian, Yu-Han; Xiao, Qian; Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2018)
A new species of the genus Nemoura, N. latilongispina sp. nov. from Chuxiong Yi Autonomous Prefecture of Yunnan Province, southwestern China is described and illustrated. The new species is characterized by ventral sclerite of epiproct extended laterally, forming upcurved plates fringed with long spines along upper margin, and by the strongly sclerotized, fork-shaped cercus.